Macierzyństwo nastoletnich kobiet w aspekcie społecznym, psychologicznym i prawnym = Childbearing among teenage women as seen from the social, psychological and legal points of view - Bałanda-Bałdyga, Agnieszka; Łepecka-Klusek, Celina; Pilewska-Kozak, Anna Bogusława; Pawłowska-Muc, Agnieszka Konstancja; Stadnicka, Grażyna (Journal of Education, Health and Sport, 2016)
Bałanda-Bałdyga Agnieszka, Łepecka-Klusek Celina, Pilewska-Kozak Anna B., Pawłowska-Muc Agnieszka K., Stadnicka Grażyna. Macierzyństwo nastoletnich kobiet w aspekcie społecznym, psychologicznym i prawnym = Childbearing among teenage women as seen from the social, psychological and legal points of view. Journal of Education, Health and Sport. 2016;6(6):531-542. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56481 http://ojs.ukw.edu.pl/index.php/johs/article/view/3640 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 27.06.2016. Macierzyństwo nastoletnich kobiet w aspekcie społecznym, psychologicznym i prawnym Childbearing among teenage women as seen from the social, psychological and legal points of view Agnieszka Bałanda-Bałdyga1, Celina Łepecka-Klusek2, Anna B. Pilewska-Kozak2, Agnieszka K. Pawłowska-Muc3, Grażyna Stadnicka1 1/ Zakład Podstaw Położnictwa, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, 20-081 Lublin ul. Staszica 4/6; 2/ Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, 20-037 Lublin al. Racławickie 23. 3/ Powiatowe Centrum Medyczne Sp. z.o.o., 05-600 Grójec ul. Piotra Skargi 10 dr n. o zdrowiu Agnieszka Bałanda-Bałdyga, dr hab. n. med. Celina Łepecka-Klusek, dr n. med. Anna B. Pilewska-Kozak, mgr Agnieszka K.Pawłowska-Muc, dr n. med. Grażyna Stadnicka Streszczenie Pomimo obserwowanych zmian w preferencjach, dotyczących zakładania rodziny i rosnących aspiracji życiowych młodych ludzi w zakresie poziomu wykształcenia oraz statusu zawodowego i społecznego, nadal obserwuje się wiele tysięcy urodzeń dzieci przez nastoletnie kobiety, w tym także w krajach wysokorozwiniętych. Przyczyn tej sytuacji upatruje się zarówno w akceleracji rozwojowej młodzieży, jak i w zmianie obyczajowości seksualnej, a szczególnie obniżaniu się wieku inicjacji seksualnej. Ze względu na konsekwencje przedwczesnego macierzyństwa zagadnienie to trzeba rozpatrywać wieloaspektowo. Konsekwencje bowiem nie są wyłącznie problemem osobistym dziewczyny, ale również rodziny, szkoły, społeczeństwa. Moment pojawienia się nowego życia, wraz z całym okresem ciąży i porodu, wydaje się być jednym z ważniejszych wydarzeń, rzutującym na całą przyszłość kobiety, jej dziecka i rodziny. W pracy omówiono zagadnienie dotyczące nastoletniego macierzyństwa z punktu widzenia socjologii, psychologii i prawa. Zaprezentowano najważniejsze skutki i związane ze zbyt młodym rodzicielstwem komplikacje życia codziennego nastoletnich matek, wynikające w szczególności z braku niezależności finansowej i pełnienia roli uczennicy. Celem pracy było ukazanie problemu macierzyństwa nastoletnich kobiet w aspekcie społecznym, psychologicznym oraz prawnym. Słowa kluczowe: ciąża nastolatek, wsparcie społeczne, adaptacja psychologiczna, prawo. Abstract Although young peoples’ preferences concerning parenthood and aspirations regarding education, social and proffesional status are changing, every year teenage women are still giving birth to thousands of children in both underdeveloped and developed countries. The reason for this may be a faster development of teenagers as well as changes in sexual behaviour, especially earlier sexual initiation. The issue has to be looked upon from different standpoints due to various consequences of premature motherhood. Those consequences are not only of personal nature of a mother, but they affect family, school and society too. The moment of creating a new life, together with pregnancy and child delivery, seems to be one of the most important events that will shape the future of a mother, her child and close family. This article focuses on teenage childbearing as it is seen by sociologist, psychologist and lawyers. It also presents the most crucial consequences of becoming a parent too early in life which originate in being financially dependant and the student status. The aim of this study is to present the problem of teenage motherhood from sociological, psychological and legal standpoint. Keywords: adolescent pregnancy, social support, adaptation psychological, law.